FUNGSI IDENTIFIKASI SIDIK JARI DALAM PENGUNGKAPAN TINDAK PIDANA DI POLRESTA TENGGARONG - Joko Hadi Aprianto (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTFingerprints that nothing is equal to each other. Human fingerprints will not change from birth to death, and also the prints can be formulated, so it can be administered and stored and retrievable With the efficacy of existing in scales finger can be used as evidence in court, which could add to the confidence of judges in deciding cases and is an important clue to determine who the perpetrators of criminal acts that have occurred.